Development of a proposal for an online free access termbank for translation trainees at the Translation Office of the UCSG - Freire Zabala, Kevin Roberto (2017)
The Translation Office of UCSG offers the possibility to students to further their skills by becoming trainees. Many of these new translators are assigned with several documents from different linguistic fields and this task can present difficulties for inexperienced translators. The aim of this research project is to propose the creation of an online termbank for inters of the Translation Department. This reference tool will help to overcome the most common mistakes done by interns and improve the quality of the translations they render. This research was performed under a mixed approach, as it required deep analysis over facts and numerical information in order to reach the aims proposed, which lead to conclude how important it is to implement of a termbank and the possible benefits that it may bring in the future.